Pengaruh Kualitas Layanan terhadap Kepuasan dan Kepercayaan di Rumah Sakit Bunda Kandangan Surabaya - Kartikasari, Dwi; Dewanto, Aryo; Rochman, Fatchur (Jurnal Aplikasi Manajemen, 2014)
This study aims to determine the effect of hospital service quality on satisfaction and trust of the patients. Data were collected using questionnaires. Questionnaires were given to patients in the hospitalization unit of RSBK. The sample of this study is 121 people. Data were analyzed by Structural Equation Modeling (SEM) with SPSS AMOS software. The study shows that service quality has a direct and indirect effect on patients'trust. Service quality has indirect effects on patient's trust through patient satisfaction as interviening variable. There is a significant direct effect of service quality on patients' satisfaction, but there is no significant indirect effect of service quality on patients'satisfaction through patients'trust.